Dampak Kebijakan Domestic Market Obligation terhadap Volume Ekspor Batu Bara Indonesia: Studi Kasus Korea Selatan dan Filipina - Damayanti, Melissa; Hendrati, Ignatia Marta; Wardaya, Wirya (Jurnal EMT KITA, 2026)
Indonesia is one of the major coal suppliers in the international market and plays an important role in meeting the energy demand of many countries in Asia. To ensure domestic energy availability, the Indonesian government implemented the Domestic Market Obligation (DMO) policy, which requires coal producers to allocate a portion of their production to the domestic market. This policy potentially affects the dynamics of Indonesia’s coal exports to its trading partners. This study aims to analyze the impact of the DMO policy on Indonesia’s coal export volume to South Korea and the Philippines using a quantitative approach through multiple linear regression analysis. The data used in this study consist of time series data for the period 2000–2022, including the GDP of the destination countries, Indonesia’s domestic coal consumption, and a dummy variable representing the DMO policy. The estimation results indicate that the GDP of South Korea and the Philippines has a positive and significant effect on Indonesia’s coal export volume, suggesting that economic growth in the destination countries increases energy demand and subsequently raises coal import demand. In contrast, Indonesia’s domestic coal consumption does not show a significant effect on export volume. Meanwhile, the DMO dummy variable has a negative and significant effect on Indonesia’s coal exports to both countries. These findings indicate that the DMO policy, which prioritizes domestic energy supply, indirectly constrains Indonesia’s coal export capacity. From the perspective of Non-Tariff Measures, the policy empirically exhibits characteristics similar to non-tariff trade barriers because it affects the quantity of exports available in the international market.